2016
DOI: 10.1080/10888438.2016.1199554
|View full text |Cite
|
Sign up to set email alerts
|

N170 Tuning in Chinese: Logographic Characters and Phonetic Pinyin Script

Abstract: In alphabetic languages, print consistently elicits enhanced, left-lateralized N170 responses in the event-related potential compared to control stimuli. In the current study, we adopted a cross-linguistic design to investigate N170 tuning to logographic Chinese and to pinyin, an auxiliary phonetic system in Chinese. The results demonstrated that logographic characters elicit a left-lateralized print-tuning effect in Chinese readers only. Crucially, the observed tuning effect is clearly driven by script famili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 50 publications
(72 reference statements)
1
7
0
Order By: Relevance
“…Although both Chinese and Japanese groups showed left lateralization, the degree of left lateralization was higher in the native Chinese group (see Table 4). These results replicated past findings of left lateralization of N170 in a repetition detection task for skilled readers (Maurer et al, 2008; Qin et al 2016), and bilateral N170 response to Chinese characters in L2 Chinese readers with alphabetic L1 (Yum et al, 2018). This pattern of results may relate to the participants’ visual experience with Chinese characters – interpreted as a basic level of visual familiarity that depended on amount of script exposure rather than access to phonological or lexical representations.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although both Chinese and Japanese groups showed left lateralization, the degree of left lateralization was higher in the native Chinese group (see Table 4). These results replicated past findings of left lateralization of N170 in a repetition detection task for skilled readers (Maurer et al, 2008; Qin et al 2016), and bilateral N170 response to Chinese characters in L2 Chinese readers with alphabetic L1 (Yum et al, 2018). This pattern of results may relate to the participants’ visual experience with Chinese characters – interpreted as a basic level of visual familiarity that depended on amount of script exposure rather than access to phonological or lexical representations.…”
Section: Discussionsupporting
confidence: 89%
“…There are also studies that found a left-lateralized topography. Interestingly, the great majority, if not all, of these reports were based on content-irrelevant tasks such as color-matching (Cao et al, 2011; Lin et al, 2011; Xue et al, 2019; Zhao et al, 2012), size judgment (Lu et al, 2011), and repetition detection (Maurer et al, 2008; Qin, Maurits & Maassen, 2016). Taken together, these results suggested that the N170 effect can be found across different writing systems, and its lateralization may not be a distinct characteristic of a particular writing system as previously thought.…”
Section: Introductionmentioning
confidence: 99%
“…It has been long contested whether alphabetic vs. logographic languages are processed differently in the brain, and a few studies tried to investigate this in relation to the N170 (Wong et al, 2005 ; Maurer et al, 2008b ; Cao et al, 2011 ; Lin et al, 2011 ; Qin et al, 2016 ). The authors aimed to answer whether the type of orthographic script modulates the lateralization of print specialization or whether it is entirely dependent on script familiarity of the participants involved in the experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The N170 literature has been highly inconsistent in the reporting of cross-linguistic laterality differences, as well as amplitude differences among words, pseudowords, and consonant strings within the same script. Although a larger number of N170 studies concurred with the fMRI literature in finding bilateral or right-lateralized N170 activity for logographic scripts (Chen, Bukach, & Wong, 2013;Liu & Perfetti, 2003;Wang & Maurer, 2017;Zhang et al, 2011;Niermeyer et al, 2018), reports of left-lateralized N170 activity for logographic reading are not uncommon (Lin et al, 2011;Qin, Maurits, & Maassen, 2016;Wong et al, 2005;Maurer, Zevin, & McCandliss, 2008). Similarly, among studies that compared N170 activation for words, pseudowords, and consonant strings within the same script, some reported enhanced N170 activation for pseudowords than for words, but others failed to observe a difference, or even reported the reverse (reviewed in .…”
Section: Introductionmentioning
confidence: 71%
“…Although the additional engagement of the right occipitotemporal region in logographic reading is well supported by numerous meta-analyses of fMRI studies, the N170 literature is considerably less consistent. While some studies found that the reading of logographic scripts elicit bilateral N170 activity (Chinese: Chen, Bukach, & Wong, 2013;Liu and Perfetti, 2003;Wang & Maurer, 2017;Zhang et al, 2011;Japanese: Niermeyer et al, 2018), left-lateralized N170 responses have also been reported (Chinese: Lin et al, 2011;Qin, Maurits, and Maassen, 2016;Wong et al, 2005;Zhao et al, 2012 (marginally left-lateralized); Japanese Kanji: Horie et al, 2012; Maurer, Zevin, & McCandliss, 2008). In contrast, left-lateralized N170 effects is generally observed in alphabetic scripts such as English (Bentin et al, 1999), French (Mahe et al, 2012, and German (Maurer et al, 2005).…”
Section: Cross-linguistic Differences In Word N170 Lateralizationmentioning
confidence: 99%